PprA Protein Inhibits DNA Strand Exchange and ATP Hydrolysis of Deinococcus RecA and Regulates the Recombination in Gamma-Irradiated Cells - Rajpurohit, Yogendra Singh; Sharma, Dhirendra Kumar; Misra, Hari S. (Frontiers in Cell and Developmental Biology, 2021)
DrRecA and PprA proteins function are crucial for the extraordinary resistance to γ-radiation and DNA strand break repair in Deinococcus radiodurans. DrRecA mediated homologous recombination help in DNA strand break repair and cell survival, while the PprA protein confers radio-resistance via its roles in DNA repair, genome maintenance, and cell division. Genetically recA and pprA genes interact and constitute an epistatic group however, the mechanism underlying their functional interaction is not clear. Here, we showed the physical and functional interaction of DrRecA and PprA protein both in solution and inside the cells. The absence of the pprA gene increases the recombination frequency in gamma-irradiated D. radiodurans cells and genomic instability in cells growing under normal conditions. PprA negatively regulates the DrRecA functions by inhibiting DrRecA mediated DNA strand exchange and ATPase function in vitro. Furthermore, it is shown that the inhibitory effect of PprA on DrRecA catalysed DNA strand exchange was not due to sequestration of homologous dsDNA and was dependent on PprA oligomerization and DNA binding property. Together, results suggest that PprA is a new member of recombination mediator proteins (RMPs), and able to regulate the DrRecA function in γ-irradiated cells by protecting the D. radiodurans genome from hyper-recombination and associated negative effects.